Competency-Based Accounting Education, Training, and Certification : An Implementation Guide - Borgonovo, Alfred; Friedrich, Brian; Wells, Michael (Washington, DC: World Bank, 2019)
This guide is designed to assist all those who are responsible for providing or overseeing formal education or practical experience that forms part of the initial professional development of aspiring professional accountants, or the continuing professional development of professional accountants. It is particularly relevant to professional accountancy organizations. It is also intended for policy makers and regulators who determine which organizations are licensed to certify professional accountants and related specializations, for example, audit professionals. The purpose of the guide is to • increase understanding of the gap between the current skills of many accountants in some regions and the skills that are relevant in increasingly digitized and globalized economies; • convey the essential features of Competency-Based Accounting Education, Training, and Certification (CBAETC); • provide a common reference framework for organizations pursuing CBAETC and the consultants working with them; • assist countries in developing in-country plans and implementing in-country processes that produce accountants with higher-order skills relevant to their economy’s rapidly evolving needs; and • improve financial reporting, auditing, and regulation. This guide complements and builds on International Education Standards (IES™) of the International Accounting Education Standards Board™ (IAESB™).